Explaining Cross-Language Asymmetries in Prosodic Processing: The Cue-Driven Window Length Hypothesis. (December 2019) - Ortega-Llebaria, Marta; Olson, Daniel J.; Tuninetti, Alba
Cross-language studies have shown that English speakers use suprasegmental cues to lexical stress less consistently than speakers of Spanish and other Germanic languages ; accordingly, these studies have attributed this asymmetry to a possible trade-off between the use of vowel reduction and suprasegmental cues in lexical access. We put forward the hypothesis that this "cue trade-off" modulates intonation processing as well, so that English speakers make less use of suprasegmental cues in comparison to Spanish speakers when processing intonation in utterances causing processing asymmetries between these two languages. In three cross-language experiments comparing English and Spanish speakers' prediction of hypo-articulated utterances in focal sentences and reporting speech, we have provided evidence for our hypothesis and proposed a mechanism, the Cue-Driven Window Length model, which accounts for the observed cross-language processing asymmetries between English and Spanish at both lexical and utterance levels. Altogether, results from these experiments illustrated in detail how different types of low-level acoustic information (e.g., vowel reduction versus duration) interacted with higher-level expectations based on the speakers' knowledge of intonation providing support for our hypothesis. These interactions were coherent with an active model of speech perception that entailed real-time adjusting to feedback and to information from the context, challenging more traditional models that consider speech perception as a passive, bottom-up pattern-matching process.